Impact of comorbidity rates of lumbar spondylosis, knee osteoarthritis, and osteoporosis on physical QOL and risk factors for poor physical QOL in middle-aged and elderly people. Issue 2 (3rd March 2020) - Imagama, Shiro; Ando, Kei; Kobayashi, Kazuyoshi; Seki, Taisuke; Hamada, Takashi; Machino, Masaaki; Ota, Kyotaro; Tanaka, Satoshi; Morozumi, Masayoshi; Kanbara, Shunsuke; Ito, Sadayuki; Ishiguro, Naoki; et al.
Abstract: Purpose: To examine effects of combined osteoporosis (P), knee osteoarthritis (K-OA), and lumbar spondylosis (L-OA) on quality of life (QOL), and identify risk factors for poor QOL. Methods: 1021 subjects (440 males, 581 females, mean age: 63.4 years) were prospectively included. Osteoporosis (%YAM ≤70%), K-OA (Kellgren-Lawrence grade ≥2), and L-OA (Nathan class ≥3) were defined. Subjects were divided into groups 0 to 3 based on the number of comorbid diseases, and into groups P, K, and L (one disease), PK, PL, and KL (two diseases), and PKL (three diseases). Clinical variables and QOL were compared, and risk factor analysis was conducted. Results: BMI, muscle strength, pain, and spinal inclination significantly increased and physical QOL worsened with more comorbidities. Though age did not differ among disease groups, BMI was significantly higher in groups K and L than in group P. Groups including subjects with L-OA had significantly lower lumbar lordosis and larger spinal inclination. In multivariate logistic regression analysis adjusted for age and gender, group KL, spinal inclination, gait speed, grip strength, and pain were risk factors for poor physical QOL. Conclusion: Increased comorbidity has a negative impact on physical QOL, and six risk factors for poor physical QOL were identified.